Fitokimia dan Aktivitas Antiradikal DPPH Seduhan Daun Kayu Jawa (Lannea coromandelica) - Jusna; Nasrudin; Abraham Rahman (Jurusan Pendidikan Kimia FKIP Universitas Halu Oleo, Jl. HEA. Mokodompit Kampus Hijau Bumi Tridharma Andounohu Kendari, Gedung MIPA FKIP UHO Sulawesi Tenggara – Indonesia, 2022)
Research on Phytochemicals and Antiradical Activities of DPPH Stew of Javanese Wood Leaves (Lannea coromandelica) has been carried out. This study aims to determine thephytochemical description of the infusionof Javanese leaves (L. coromandelica), todetermine the operating time in determining the anti-radical activity of the infusion of Javanese leaves (L. coromandelica) and the description of the anti-radical activity of DPPH steeped of Javanese leaves (L. coromandelica). The method used to test the secondary metabolites of Javanese wood leaves are phytochemicals and antiradical with the DPPH method. Javanese wood leaves used are dried Javanese wood leaves that have been mashed. A total of 5 g of Javanese wood leaves were brewed with 3 repetitions with gallon water as solvent. The extracts were then tested for phytochemicals and antiradical. The results of the phytochemical test showed that the steeped extract of the leaves of Java wood contained saponins, flavonoids and polyphenols. Operating Time results show 30 minutes. The steeping extract of Javanese wood leaves has a very weak antiradical with an IC50 value of 408, 95 ± 0.0752 ppm.